Roles of Fibroblast Growth Factors and Their Therapeutic Potential in Treatment of Ischemic Stroke - Dordoe, Confidence; Chen, Keyang; Huang, Wenting; Chen, Jun; Hu, Jian; Wang, Xue; Lin, Li (Frontiers in Pharmacology, 2021)
Stroke is the leading cause of death worldwide, and its treatment remains a challenge. Complex pathological processes are involved in stroke, which causes a reduction in the supply of oxygen and energy to the brain that triggers subsequent cascade events, such as oxidative stress, inflammatory responses and apoptosis, resulting in brain injury. Stroke is a devastating disease for which there are few treatments, but physical rehabilitation can help improve stroke recovery. Although there are very few treatments for stroke patients, the discovery of fibroblast growth factors (FGFs) in mammals has led to the finding that FGFs can effectively treat stroke in animal models. As presented in this review, FGFs play essential roles by functioning as homeostatic factors and controlling cells and hormones involved in metabolism. They could be used as effective therapeutic agents for stroke. In this review, we will discuss the pharmacological actions of FGFs on multiple targets, including their ability to directly promote neuron survival, enhance angiogenesis, protect against blood-brain barrier (BBB) disruption, and regulate microglial modulation, in the treatment of ischemic stroke and their theoretical mechanisms and actions, as well as the therapeutic potential and limitations of FGFs for the clinical treatment of stroke.